2021
DOI: 10.1111/ddi.13284
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA of preservative ethanol performed better than water samples in detecting macroinvertebrate diversity using metabarcoding

Abstract: Aim High‐throughput pipelines supported by eDNA metabarcoding have been applied in various freshwater ecosystems. Both eDNA in ethanol (EtOH) samples (ES‐eDNA) and in water samples (WS‐eDNA) can provide comprehensive classification lists with good taxonomic resolution and coverage for determining freshwater biodiversity and biomonitoring. But, the advantages of ES‐eDNA metabarcoding over WS‐eDNA metabarcoding remain unclear for routine assessments of diversity of benthic macroinvertebrates in streams. Location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 88 publications
2
14
0
Order By: Relevance
“…Beta diversity analyses also indicated that different taxa were detected using different ethanol treatments for the Horniman invasive sponge. This reaffirms findings of studies on bulk invertebrate samples (Zizka et al, 2018; Derycke et al, 2021; Persaud et al, 2021; Wang et al, 2021) and marine sponges (Jeunen et al, 2019) where eDNA from ethanol preservative detected different taxa to DNA from tissue, although eDNA from ethanol preservative generally detected more taxa than bulk invertebrate tissue but less taxa than marine sponge tissue.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Beta diversity analyses also indicated that different taxa were detected using different ethanol treatments for the Horniman invasive sponge. This reaffirms findings of studies on bulk invertebrate samples (Zizka et al, 2018; Derycke et al, 2021; Persaud et al, 2021; Wang et al, 2021) and marine sponges (Jeunen et al, 2019) where eDNA from ethanol preservative detected different taxa to DNA from tissue, although eDNA from ethanol preservative generally detected more taxa than bulk invertebrate tissue but less taxa than marine sponge tissue.…”
Section: Discussionsupporting
confidence: 86%
“…Residual ethanol in tissue can retain unique DNA that may leech from tissue into ethanol (Zizka et al, 2018; Marquina et al, 2019; Jeunen et al, 2019; Derycke et al, 2021; Persaud et al, 2021; Wang et al, 2021), but also react with buffers used for DNA extraction and/or inhibit PCR amplification downstream (Schrader et al, 2012). Our DNA concentration results seem to indicate that residual ethanol contained DNA unique and/or additional to that present in sponge tissue (at least for the Horniman invasive sponge) as higher total DNA yields and post-PCR DNA concentrations were observed with the wet ethanol treatment.…”
Section: Discussionmentioning
confidence: 99%
“…DNA metabarcoding of eDNA from water samples often register more macroinvertebrate taxa than approaches using morphological identification (Deiner et al, 2016;Wang et al, 2021). Several studies have also mapped biodiversity by a combination of DNA metabarcoding of aquatic eDNA and DNA from tissues of bulk samples.…”
Section: Introductionmentioning
confidence: 99%
“…DNA metabarcoding of DNA from preservative fluids, first shown by Shokralla et al (2010), is one such method as it avoids specimen destruction. Although barcoding of preservative ethanol has shown some promising results compared to barcoded specimens of the corresponding bulk samples (Hajibabaei et al, 2012), and to eDNA from water samples (Wang et al, 2021), a recent study showed few shared taxa compared to bulk tissue samples (Persaud et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is no guarantee that a protocol yielding promising results for one system would also perform well for other water bodies. Regardless of these challenges, many water eDNA metabarcoding workflows are now undergoing calibration and refinement (Cristescu & Hebert, 2018;Kumar et al, 2020;McGee et al, 2019;Ruppert et al, 2019;Y. Wang et al, 2021;Zinger et al, 2019).…”
Section: Introductionmentioning
confidence: 99%